Confinement in electron heated plasmas in Wendelstein 7-X and ASDEX Upgrade; the necessity to control turbulent transport. (14th December 2021) - Beurskens, M.N.A.; Angioni, C.; Bozhenkov, S. A.; Ford, O.; Kiefer, C.; Xanthopoulos, P.; Turkin, Y.; Alcusón, J.A.; Baehner, J.P.; Beidler, C.; Birkenmeier, G.; Fable, E.; et al.
Abstract: In electron (cyclotron) heated plasmas, in both ASDEX Upgrade ( L -mode) and Wendelstein 7-X, clamping of the ion temperature occurs at T i ∼ 1.5 keV independent of magnetic configuration. The ions in such plasmas are heated through the energy exchange power as n e 2 ( T e − T i ) / T e 3 / 2, which offers a broad ion heating profile, similar to that offered by alpha heating in future thermonuclear fusion reactors. However, the predominant electron heating may put an additional constraint on the ion heat transport, as the ratio T e / T i > 1 can exacerbates ITG/TEM core turbulence. Therefore, in practical terms the strongly 'stiff' core transport translates into T i -clamping in electron heated plasmas. Due to this clamping, electron heated L -mode scenarios, with standard gas fueling, in either tokamaks or stellarators may struggle to reach high normalized ion temperature gradients required in a compact fusion reactor. The comparison shows that core heat transport in neoclassically optimized stellarators is driven by the same mechanisms as in tokamaks. The absence of a strong H -mode temperature edge pedestal in stellarators, sofar (which, like in tokamaks, could lift the clamped temperature-gradients in the core), puts a strong requirement on reliable and sustainable core turbulence suppression techniques in stellarators.